2023
DOI: 10.1111/jnc.15882
|View full text |Cite
|
Sign up to set email alerts
|

METTL14 is decreased and regulates m6A modification of α‐synuclein in Parkinson's disease

Abstract: N6-methyladenosine (m6A), an emerging modification of messenger RNA, has been implicated in many biological processes. However, its role in Parkinson's disease (PD) remains largely unknown. Here, we investigated the role of m6A modification and its underlying mechanism in PD. First, 86 individuals with PD and 86 healthy controls were recruited from a pilot multicenter cohort. Levels of m6A and its modulators in peripheral blood mononuclear cells of patients with PD and controls were measured using an m6A RNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This escalation contributes to oxidative stress, an increase in calcium influx, and ultimately, it accelerates the degeneration or cell death of these dopaminergic neurons [ 92 ]. In another study, METTL3, METTL14, and YTHDF2 were significantly downregulated in PD patient blood mononuclear cells with METTL14 being the main factor involved in the abnormal m6A modification of α-synuclein mRNA [ 93 ]. Mettl14 targets and regulates the expression of the α-synuclein gene by binding an m6A motif in the coding region which eventually modifies α-synuclein mRNA and weakens its stability.…”
Section: Rna Modifications In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This escalation contributes to oxidative stress, an increase in calcium influx, and ultimately, it accelerates the degeneration or cell death of these dopaminergic neurons [ 92 ]. In another study, METTL3, METTL14, and YTHDF2 were significantly downregulated in PD patient blood mononuclear cells with METTL14 being the main factor involved in the abnormal m6A modification of α-synuclein mRNA [ 93 ]. Mettl14 targets and regulates the expression of the α-synuclein gene by binding an m6A motif in the coding region which eventually modifies α-synuclein mRNA and weakens its stability.…”
Section: Rna Modifications In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Mettl14 targets and regulates the expression of the α-synuclein gene by binding an m6A motif in the coding region which eventually modifies α-synuclein mRNA and weakens its stability. Spearman correlation analysis showed METTL14 levels inversely correlated with plasma α-synuclein concentrations and motor function of PD patients [ 93 ]. Furthermore, the advancement in RNA sequencing capabilities has facilitated the detailed exploration of RNA editing occurrences across the whole transcriptome, offering deeper insights into A-to-I editing in various diseases.…”
Section: Rna Modifications In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The excessive loss of dopaminergic neurons occurs before the onset of motor symptoms in PD patients [ 217 ]. m6A modification variants were found in PD patients [ 218 ], and METTL3, METTL14, and YTHDF2 mRNA levels were lower in PD patients, suggesting that PD pathogenesis may be regulated via m6A modification [ 154 ].…”
Section: Rna M6a In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The conditional knockout of METTL14 significantly reduced the overall mRNA m6A levels and downregulated Nurr1, pitx3, and EN1 expressions in the substantia nigra region, which was associated with behavioral motor impairment [ 158 ]. Furthermore, METTL14 regulates the stability of α-syn mRNA [ 154 ]. The HNRNPC expression level is low in PC12 cells, while HNRNPC overexpression inhibits apoptosis and immune inflammation [ 159 ].…”
Section: Rna M6a In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The expression of m6a-related proteins, including METTL3, METTL14, and YTHDF2, was also notably downregulated. Further research indicated that METTL14 influences the stability of α-Syn mRNA and modulates α-Syn expression in an m6A-dependent manner, potentially offering valuable diagnostic information for PD ( He et al, 2023 ).…”
Section: M6a and Parkinson’s Diseasementioning
confidence: 99%